2020
DOI: 10.1088/1755-1315/572/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potential Probiotic Lactic Acid Bacteria from Tempe and Tape

Abstract: Probiotics are living organisms with many beneficial effects on the health of host if consumed in sufficient quantities. These beneficial effects have been initiating efforts directed towards exploring strains Lactic Acid Bacteria (LAB) as probiotic from fermented food such tempe and tape. Although several groups of microorganism from fermented foods such as tempe and tape were reported, the potential LAB derived from those food sources is limited. The aim of this study was to assess probiotic candidate from L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The tolerance of P. acidilactici to higher bile concentrations is consistent with other findings in the literature regarding non-poultry-derived isolates [23]. However, W. paramesenteroides non-poultryderived isolates had varying ability to grow in bile, with many falling into moderate to poor categories of bile growth performance [24,25]. Some of these grew much poorer in bile compared to Lactobacillus species in the same test, although none were the same species of Lactobacillus used in our study [25].…”
Section: Discussionsupporting
confidence: 90%
“…The tolerance of P. acidilactici to higher bile concentrations is consistent with other findings in the literature regarding non-poultry-derived isolates [23]. However, W. paramesenteroides non-poultryderived isolates had varying ability to grow in bile, with many falling into moderate to poor categories of bile growth performance [24,25]. Some of these grew much poorer in bile compared to Lactobacillus species in the same test, although none were the same species of Lactobacillus used in our study [25].…”
Section: Discussionsupporting
confidence: 90%
“…The survival rate of the isolate is on par with previous studies by Feng et al ( 2017 ) and Guan et al ( 2017 ) with results showing a higher potential than that showed by Lactobacillus plantarum (No. 14) (Nagata et al, 2009 ), Lactobacillus crustorum KH isolated from Iranian dairy products (Sharafi et al, 2014 ), and LAB strain isolated from poultry products and tempeh (Reuben et al, 2019 ; Sulistiani et al, 2020 ). The isolate showed a good survival rate under low pH and ox gall conditions, above 90% at the last hour of incubation at varying concentrations of ox gall, which is higher than the previously reported studies (Liong and Shah, 2005 ; Succi et al, 2005 ; Chen, 2012 ; Hassanzadazar et al, 2012 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%